Letter from Robert S. Mulliken to Harrison Shull, 1950 - Mulliken, Robert Sanderson (1950)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists, where Mulliken expresses puzzlement over recent abstracts on wave functions published in the Physics Abstracts by unnamed German and Japanese authors.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Wave functions; Quantum theory; Chemists; Quantum chemistry; Nobel Prize winners; Physicists; Chemistry, Physical and theoretical